Eating Disorders and Their Putative Risk Factors Among Female German Professional Athletes. (31st March 2015) - Thiemann, Pia; Legenbauer, Tanja; Vocks, Silja; Platen, Petra; Auyeung, Bonnie; Herpertz, Stephan
Abstract This study examines putative non‐sport‐specific and sport‐specific risk factors for eating disorders (ED) among groups of professional female athletes versus non‐athletes. In detail, societal pressure to be thin, its internalisation, body dissatisfaction, sports pressure and early specialisation were investigated. The cross‐sectional study included 46 aesthetic and 62 ball game sports athletes, and 108 age‐matched non‐athletes. Study methods comprised a clinical interview to detect ED and questionnaires. More athletes from aesthetic (17%) than from ball game sports (3%) and non‐athletes (2%) suffered from ED. Aesthetic sports athletes did not differ from non‐athletes in non‐sport‐specific factors but obtained higher levels than ball game sports athletes in sport‐specific variables (p < .01). All factors together accounted for 57.3% of variation in disordered eating, with sports pressure and body dissatisfaction as significant predictors. The results confirm ED risk for German aesthetic athletes and indicate the importance of sports pressure and body dissatisfaction in explaining athletes' vulnerability. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.